NUF2 overexpression contributes to epithelial ovarian cancer progression via ERBB3-mediated PI3K-AKT and MAPK signaling axes - Leng, Ruobing; Meng, Yunfang; Sun, Xiaomei; Zhao, Yingzi (Frontiers in Oncology, 2022)
NDC80 kinetochore complex component (NUF2) is upregulated and plays an important role in various human cancers. However, the function and mechanism of NUF2 in epithelial ovarian cancer (EOC) remain unclear. We showed that NUF2 was significantly upregulated in EOC tissues and cell lines, and high NUF2 expression was associated with FIGO stage, pathological grade and poor EOC prognosis. NUF2 downregulation decreased cell proliferation, migration, invasion and tumor growth in nude mice. RNA sequencing studies showed that NUF2 knockdown inhibited several genes enriched in the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)-AKT serine/threonine kinase (AKT) and mitogen-activated protein kinase (MAPK) signaling pathways. Erb-B2 receptor tyrosine kinase 3 (ERBB3) was the key factor involved in both of the above pathways. We found that ERBB3 silencing could inhibit EOC progression and repress activation of the PI3K-AKT and MAPK signaling pathways. Furthermore, the exogenous overexpression of ERBB3 partially reversed the inhibitory effects on EOC progression induced by NUF2 downregulation, while LY294002 and PD98059 partially reversed the effects of ERBB3 upregulation. These results showed that NUF2 promotes EOC progression through ERBB3-induced activation of the PI3K-AKT and MAPK signaling axes. These findings suggest that NUF2 might be a potential therapeutic target for EOC.